Masjid Aur Menanjung, Kampung Aur Menanjung, Daerah Yaring, Pattani, Thailand / [lukisan teknik] - Hamdie Basri; Mohd. Nakia Nawi; Mohd. Shazril Shafiee; Saiful Razman Shaadan; Wan Yuzaini Wan Yahya; Nur Adelina Ramli (Skudai : Universiti Teknologi Malaysia, 1997)
Kajian Lukisan Terukur (Jabatan senibina) - Universiti Teknologi Malaysia, 1997